SISTEM PENGENDALIAN PENGELUARAN KAS PADA PT. KIA MOTORS - Silvester Saman (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2019)
This study aims to determine the implementation of internal cash control systems at PT. KIA MOTORS Makassar Branch. The method is a Comparative analysis method by comparing the theory with the internal control system of cash expenditures which applied by PT. KIA MOTORS Makassar Branch. The result of the study is the company's cash expenditures derived from two main sources, namely: spending cash with cash through a petty cash funding system and by check. The internal control system disburses cash with petty cash and checks at PT. KIA MOTORS INDONESIA Branch Makassar is good enough. This is because the company has fulfilled the elements of existing internal control.